Microbial ice nucleators scavenged from the atmosphere during simulated rain events. (August 2017) - Hanlon, Regina; Powers, Craig; Failor, Kevin; Monteil, Caroline L.; Vinatzer, Boris A.; Schmale, David G.
Abstract: Rain and snow collected at ground level have been found to contain biological ice nucleators. These ice nucleators have been proposed to have originated in clouds, where they may have participated in the formation of precipitation via ice phase nucleation. We conducted a series of field experiments to test the hypothesis that at least some of the microbial ice nucleators (prokaryotes and eukaryotes) present in rain may not originate in clouds but instead be scavenged from the lower atmosphere by rainfall. Thirty-three simulated rain events were conducted over four months off the side of the Smart Road Bridge in Blacksburg, VA, USA. In each event, sterile water was dispensed over the side of the bridge and recovered in sterile containers in an open fallow agricultural field below (a distance of ∼55 m). Microbes scavenged from the simulated rain events were cultured and their ice nucleation activity was examined. Putative microbial ice nucleators were cultured from 94% (31/33) of the simulated rain events, and represented 1.5% (121/8331) of the total colonies assayed. Putative ice nucleators were subjected to additional droplet freezing assays, and those confirmed through these repeated assays represented 0.4% (34/8331) of the total. Mean CFUs scavenged by simulated rain ranged from 2 to 267 CFUs/mL. Scavenged ice nucleators belong to a number of taxa including the bacterial genera Pseudomonas, Pantoea, and Xanthomonas, and the fungal genera Fusarium, Humicola, and Mortierella . An ice-nucleating strain of the fungal genus Penicillium was also recovered from a volumetric air sampler at the study site. This work expands our knowledge of the scavenging properties of rainfall, and suggests that at least some ice nucleators in natural precipitation events may have been scrubbed from the atmosphere during rainfall, and thus are not likely to be involved in precipitation. Highlights: Simulated rain events were conducted at ∼55 m above ground to screen for culturable ice nucleators. Putative microbial ice nucleators were cultured from 94% (31/33) of the simulated rain events. Microbes confirmed as ice nucleators in repeated assays represented 0.4% (34/8331) of the total. Ice-nucleating genera included Pseudomonas, Pantoea, Xanthomonas, Fusarium, Humicola, and Mortierella . Some microbial ice nucleators in natural rainfall may have been scrubbed from the atmosphere.